Cracking the Cytotoxicity Code: Apoptotic Induction of 10-Acetylirciformonin B is Mediated through ROS Generation and Mitochondrial Dysfunction - Huei-Chuan Shih; Mohamed El-Shazly; Yung-Shun Juan; Chao-Yuan Chang; Jui-Hsin Su; Yu-Cheng Chen; Shou-Ping Shih; Huei-Mei Chen; Yang-Chang Wu; Mei-Chin Lu (Marine Drugs, 2014)
A marine furanoterpenoid derivative, 10-acetylirciformonin B (10AB), was found to inhibit the proliferation of leukemia, hepatoma, and colon cancer cell lines, with selective and significant potency against leukemia cells. It induced DNA damage and apoptosis in leukemia HL 60 cells. To fully understand the mechanism behind the 10AB apoptotic induction against HL 60 cells, we extended our previous findings and further explored the precise molecular targets of 10AB. We found that the use of 10AB increased apoptosis by 8.9%–87.6% and caused disruption of mitochondrial membrane potential (MMP) by 15.2%–95.2% in a dose-dependent manner, as demonstrated by annexin-V/PI and JC-1 staining assays, respectively. Moreover, our findings indicated that the pretreatment of HL 60 cells with N-acetyl-l-cysteine (NAC), a reactive oxygen species (ROS) scavenger, diminished MMP disruption and apoptosis induced by 10AB, suggesting that ROS overproduction plays a crucial rule in the cytotoxic activity of 10AB. The results of a cell-free system assay indicated that 10AB could act as a topoisomerase catalytic inhibitor through the inhibition of topoisomerase IIα. On the protein level, the expression of the anti-apoptotic proteins Bcl-xL and Bcl-2, caspase inhibitors XIAP and survivin, as well as hexokinase II were inhibited by the use of 10AB. On the other hand, the expression of the pro-apoptotic protein Bax was increased after 10AB treatment. Taken together, our results suggest that 10AB-induced apoptosis is mediated through the overproduction of ROS and the disruption of mitochondrial metabolism.